Inside Cover: (4R)‐ and (4S)‐Fluoroproline in the Conserved cis‐Prolyl Peptide Bond of the Thioredoxin Fold: Tertiary Structure Context Dictates Ring Puckering (ChemBioChem 9/2013). Issue 9 (12th June 2013) - Rubini, Marina; Schärer, Martin A.; Capitani, Guido; Glockshuber, Rudi
<x xml:space="preserve">Abstract</x> The inside cover picture shows the crystal structure of the thioredoxin variant Trx1P, which contains cis‐Pro76 as the only proline residue. On p. 1053 ff., M. Rubini et al. explain how the tertiary structure dictates the cis conformation–there is endo puckering of the ring when Pro76 is replaced by either (4R)‐ or (4S)‐fluoroproline, although (4R)‐fluoroproline disfavors this conformation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>